Can Immature Granulocytes Guide Chemotherapy Decisions in Later Lines of Therapy for HER2-Negative Breast Cancer? - Ersoy, Mustafa (The European Research Journal, 2026)
Objectives: In human epidermal growth factor receptor 2 (HER2)-negative breast cancer, the need for chemotherapy often continues from the 3rd line onwards. However, these patients may experience side effects without the desired benefit due to prolonged treatments and low response rates. Our study examined immature granulocytes, routinely checked in hemogram results, for their ability to predict treatment response and toxicity. Methods: Data from patients who received third-line or later chemotherapy for HER2-negative breast cancer between 2015 and 2024 were analyzed to determine if immature granulocytes could predict treatment response, progression-free survival, or toxicity. Results: A total of 41 chemotherapy administrations were analyzed, and significant differences were observed in initial immature granulocyte counts (IG#) (P=0.046) and percentages (IG%) (P=0.006) across disease response categories. A statistically significant inverse correlation was identified between progression-free survival and both IG# (r= -0.332, P=0.034) and IG% (r= -0.323, P=0.039), indicating that elevated immature granulocyte levels were associated with shorter progression-free survival. However, regression analysis did not demonstrate a statistically significant predictive effect of IG# or IG% on progression duration (R²= 0.103, F= 2.47, P=0.098). Grade 3-4 toxicity occurred in 18 of 41 patients, but no statistically significant relationship was observed with IG#, and IG%. P=0.12 for IG# and P=0.24 for IG%). Conclusions: Pre-treatment immature granulocytes may indicate prognosis and chemotherapy resistance in breast cancer patients. They could potentially help avoid unnecessary chemotherapy, guiding patients towards targeted therapies or best supportive care.